Arthropods in coarse woody debris in jarrah forest and rehabilitated bauxite mines in Western Australia - Koch, John; Grigg, A.; Gordon, Ross; Majer, Jonathan (EDP Sciences, 2010)
Coarse woody debris (CWD) is returned to Alcoa’s rehabilitated mined areas in the jarrah forest as potential vertebrate fauna habitat, however, its value for invertebrate fauna has not been investigated. We sought to determine if CWD in rehabilitated areas supported a similar arthropod fauna to that on fallen logs in the adjacent unmined jarrah forest. Using emergence tents, sampling from logs in 5-year old and 15-year old rehabilitated forest, and in unmined forest, yielded 2266 specimens from 187 taxa. Collembola (43% of total) and Acarina (32%) were the most abundant groups, followed by Diptera (11%), Araneae (4%) and Coleoptera (3%). There were no significant differences in either taxa richness or overall abundance among the three forest types. However, community composition varied significantly. Species richness from the Araneida, Coleoptera and Diptera was highest in the 5-year old rehabilitated forest, while Collembola and Acarina were better represented in the unmined forest; this was related to changes in the environment surrounding the logs as rehabilitated forest develops, and to log condition. The composition of arthropods on logs in the 15-year old rehabilitated forest was intermediate, indicating a trend of increasing similarity to the unmined forest in arthropod fauna as the rehabilitated forest ages. We suggest that over longer time periods, CWD in rehabilitated forest will support arthropod communities similar to those found in unmined forest. Future work should determine if returning logs to mined areas facilitates the return of CWD-dependent taxa.